THE IFRS ADOPTION: CONTRIBUTION TO VALUATION THEORY - Sekar Mayangsari (Universitas Hayam Wuruk Perbanas, 2010)
The transition to IFRS has brought fundamental changes as it has impact on corporate ac- countants, public auditors, investors and its influence extends well beyond the change in accounting rules. The purpose of the paper is to investigate whether the information on IFRS adjustments is value relevant. This paper analyses value-relevance, incremental, and relative association of the effects of IFRS reconciliations reflected in earnings and owners’ equity, versus Indonesia GAAP measures. This study adopts a market value model, which relates a firm’s earnings to shareholders’ equity measured under Indonesia GAAP together with the respective IFRS reconciliation adjustment, to its market value, adding some firm specific factors to the regressions. This research uses regression to test the hypothesis. The results show that IFRS adjustments improve financial reporting quality and the capacity of financial statements to explain firm values, over and above the INDONESIA GAAP numbers. How- ever, the effect is not equally distributed given that they are more significant for larger firms. The research also reveals that the market places a high value on the earnings reconciliation adjustments but, in general, it appears that the IASB has had at least some success in provid- ing relevant information because it has the capacity to make a difference in investors’ deci- sions.